High-dose ascorbic acid synergizes with anti-PD1 therapy in non-small cell lung cancer in vitro and in vivo models - Hak Su Kim; Seung-hyun Kwon; Ok Kyung Choi; Taekyu Lim; Taekyu Lim (Frontiers in Immunology)
IntroductionImmune checkpoint inhibitors(ICIs) targeting programmed cell death protein 1 (PD1) confer significant survival benefits to patients with non-small cell lung cancer (NSCLC). However, there remains a substantial unmet need to identify therapeutic approaches to overcome resistance and provide benefits to these patients. High-dose ascorbic acid (AA) acts synergistically with many standard anticancer treatments. However, little is known about the effect of high-dose AA on improving the efficacy of anti-PD1 inhibitors in NSCLC. This study aimed to elucidate the effects of high-dose AA on anti-PD1 immunotherapy in NSCLC.MethodsThe combined effects of high-dose AA and anti-PD1 were investigated using a coculture model of H460 cells and CD8+ T cells and an LLC1 lung cancer syngeneic mouse model. To investigate the molecular mechanism, tumor tissues from mice were analyzed by comprehensive proteomic profiling using nano-LC-ESI-MS/MS.ResultsPretreatment with a high dose of AA led to enhanced the sensitivity to the cytotoxicity of CD8+ T cells derived from healthy donor for H460 cells. Additionally, the combination of anti-PD1 and high-dose AA significantly increased CD8+ T cell cytotoxicity in H460 cells. The combination of anti-PD1 and high-dose AA showed dramatic antitumor effects in a syngeneic mouse model of lung cancer by significantly reducing tumor growth and increasing CD8+ T cell-dependent cytotoxicity and macrophage activity. Comprehensive protein analysis confirmed that high-dose AA in anti-PD1-treated tumor tissues enhanced the antitumor effects by regulating various immune-related mechanisms, including the B cell and T cell receptor signaling pathways, Fc gamma R-mediated phagocytosis, and natural killer (NK) cell-mediated cytotoxicity.DiscussionOur results suggest that high-dose AA may be a promising adjuvant to potentiate the efficacy of anti-PD1 immunotherapy.